EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DAN THINK PAIR SHARE (TPS) PADA MATERI TRIGONOMETRI DITINJAU DARI KECERDASAN LOGIKA MATEMATIKA SISWA KELAS X SMA DI KABUPATEN SUKOHARJO - Sri Hartati Ningsih; Budiyono Budiyono; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from the student’s logical mathematical intelligence. The learning model compared were Group Investigation of cooperative learning model, Think Pair Share of coopeartive learning model, and direct instruction model. The type of the research was a quasi-experimental research. The population of this research was all of the X grader of State Senior High School (SMA) in Sukoharjo Regency. The sample was taken using stratified cluster random sampling, with 321 students as the sample consisting 108 students for first experiment class, 108 students for second experiment class, and 105 students for control classes. The result of research showed that: (1) group Investigation of cooperative learning model gave the best achievement among the models Think Pair Share of cooperative learning model and direct instruction model, and Think Pair Share of cooperative learning model gave better achievement than direct instruction model, (2) group of student with high logical mathematical intelligencehad the best achievement among the models group of student with middle logical mathematical intelligence and group of student with low logical mathematical intelligence, and group of student with middle logical mathematical intelligencehad better achievement than group of student with low logical mathematical intelligence, (3) at each logical mathematical intelligence categories (high, middle, and low), Group Investigation of cooperative learning model gave the best achievement among the models Think Pair Share of cooperative learning model and direct instruction model, and Think Pair Share of cooperative learning model gave better achievement than direct instruction model, (4) at each learning models (Group Investigation of cooperative learning model, Think Pair Share of cooperative learning model, and direct instruction model), group of student with high logical mathematical intelligencehad the best achievement among the models group of student with middle logical mathematical intelligence and group of student with low logical mathematical intelligence, and group of student with middle logical mathematical intelligencehad better achievement than group of student with low logical mathematical intelligence. Key words: Group Investigation, Think Pair Share, and Logical Mathematical Intelligence